Solusi Peningkatan Minat Wirausaha Dan Pengurangan Hambatan Minat Wirausaha Mahasiswa - Nimas Ayu Aang Uung Lestari; Siti Djamilah (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
The interest in entrepreneurship in Indonesia itself is still relatively low. This was evidenced by President Joko Widodo's conversation with members of the Indonesian HIPMI at the independent Palace, Jakarta, Thursday (5/4/2018). The president said that an average of 14% of the population of developed countries are entrepreneurs.